Analysis of Sheet Pile Assets Management in Musi River - Baniva, Ratih; Iqbal, Maulid M.; Fitriani, Heni (Research Centre of Inorganic Materials and Complexs, 2019)
Sheet pile, located on the bank of Musi River in Palembang, is the city master plan in the development of Palembang City. The construction of the sheet piles in Musi River was built from 2006 to 2014 but until now there is no further management on the working sheet piles. The aims of this study were to identify the management status of Musi sheet piles and to analyze the damage level that occured in Musi sheet piles in Palembang. Based on the results of the analysis, it can be obtained that the management status of the sheet pile was the authority of BBWS Sumatera VIII as the constructor and the owner of sheet pile assets, and it is planned that there will be a Musi sheet pile management program in 2019. Sheet piles were in a good condition on the components of pile cap structure, sheet pile, and platform in 16 Ilir, 9-10 Ulu, 14 Ulu, and the structure component of the sheet pile in 16 Ilir and 10 Ulu which had percentage of damage less than 10%. A good condition was also seen on the structure components of the fence support that had percentage of damage about 0,28% for ths sheet pile in 9-10 Ulu and 1,45% for the sheet pile in 14 Ulu. Sheet piles, in mildly damaged conditions, occured in sheet pile structural components of 10.38% in 11-14 Ulu. Sheet pile components in good condition and moderate damaged condition repairs can be done with preventive maintenance or minor repairs. Meanwhile, the sheet piles in a condition of heavily damaged occurred in the supporting structure of the fence by 41.82% at 16 Ilir improvements are made with corrective maintenance.